(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Research identifies the causes of inflation in the Iraqi economy after 2003, focusing on two axes, first axis focused on the most important characteristics of the Iraqi economy relevant to the subject of inflation, while the second axis has stressed the existence of the problem of inflation through the use of a set of indicators such as price index and gross domestic product at current and constant prices, as well as the indicator of monetary stability. The research found the existence of the problem of inflation in the Iraqi economy during the period of search, and find that the solutions to this problem comes through the two dimensions, the first aspect is linked to the real economy, the second is the monetary and fiscal aspects